SOFT CONTACT LENS IN MEDICINE - Тарануха О. О. (World of Medicine and Biology, 2015)
Possibility of using soft contact lens (SCL) in medical purposes always attracts ophtalmologists’ attention. The work shows that medical soft contact lens (MSCL) have an advantage in a number of cases while treating serious corneal diseases, which are resistant to commonly used methods. Nowadays, medical contact lens are used in two qualities: as bandages and as a medication carrier in order to supply the eye with medication constantly. A bandage SCL provides mechanical protection of corneal surface, fully cuts short or weakents a ‘cornea syndrome’, when applicable provides the patient with vision correction (by medical and corrective lens) and a cosmetic effect (by medical and cosmetic lens). SCL, saturated with medication, create a definite drug reserve, provide its prolonged targeted delivery to eye tissues, allows to reduce the number of instillations, make the decrease of drug dose possible while keeping its effectiveness. Today silicon-hydrogel lens are the main breakthrough in medical practice. Due to high level of oxygen permeability, SCL allow to wear them in a prolonged constant mode (without taking them off at night – maximum within 30 days). Using silicon-hydrogel soft contact lens, both as bandages and as drug reservoir, a satisfactory clinical stabilization of cornea disease or complete recovery is achieved. The quality of patients’ life is also improved.
Keywords: medical; therapeutical contact lens; silicon-hydrogel contact lens